Differences in clinical characteristics and prognosis of sudden low‐ and high‐frequency hearing loss. (7th November 2016) - Choo, Oak‐Sung; Yang, Suk Min; Park, Hun Yi; Lee, Jong Bin; Jang, Jeong Hun; Choi, Seong Jun; Choung, Yun‐Hoon
Abstract : Objectives/Hypothesis: We compared the clinical characteristics between acute low‐ and high‐frequency hearing loss (LF and HF, respectively) patients, and the efficacy of three different treatment protocols (systemic steroids, intratympanic steroid injection, and combination therapy). Study Design: Prospective, randomized controlled study. Methods: A total of 111 patients diagnosed with LF or HF were treated on an outpatient basis. Each group was randomly divided into three equal subgroups based on therapy: oral steroid, intratympanic dexamethasone injection (IT), and combination therapy. Hearing gain was estimated by comparing pre‐ and post‐treatment pure‐tone averages. Recovery rate was assessed by Clinical Practice Guideline: Sudden Hearing Loss from the American Academy of Otolaryngology–Head and Neck Surgery. Results: In comparison of chief complaints, ear fullness and hearing loss were more common in the LF and HF group, respectively ( P  = .033 and P  = .001, respectively). Hearing recovery rates were significantly different between the two groups (i.e., 74.1% [40/54] in the LF group and 45.6% [26/57] in the HF group; P  < .001). Oral steroid therapy was most effective in the LF group ( P  = .017). In the HF group, all three modalities showed similar results, although IT tended to be the most effective ( P  = .390). Conclusions: There were differences in chief complaints and treatment responses between LF and HF patients. Although they showed similar partial damage in the cochlea, the pathophysiology of LF and HF may be quite different. Level of Evidence: 1b. Laryngoscope, 127:1878–1884, 2017